Contact with immigrants in times of crisis: An exploration of the Catalan case. (October 2014) - Rodon, Toni; Franco-Guillén, Núria
Contact theory and threat group theory offer contradictory hypothesis regarding the effect of contact with immigrants. Does contact reduce or increases negative attitudes towards immigration? This article integrates both approaches and tests the effect of contact towards immigrants when different contexts are considered. We investigate the effect of the economic environment and the immigrant group size on modifying attitudes towards immigration in the context of Catalonia, which offers a complex environment where traditional hypotheses can be tested. Results show that close contact and family contact with immigrants reduce prejudices. However, mixed results are reported regarding the effect of the economic environment or the immigrant group size. Findings also show that Catalan identity is related to lower levels of negative attitudes towards immigrants, regardless of having experienced contact with foreigners. Results have implications on the impact of context when dealing with the impact of contact on attitudes towards immigration.